The Use Of Dating Application and The Relationship Development (Phenomenological Approach On Tinder) - Erna Febriani; Erick Pentury; Herdi Andrariladchi (Communicare : Journal of Communication Studies, 2022)
In this study, the researcher intends to find out how the process of developing interpersonal relationships that are woven virtually but can be maintained to a serious level. Researching a relationship that started from an online meeting on the matchmaking application (Tinder), interacted, and then decided to get married. The purpose of this research is to find out how the process of developing interpersonal relationships that are carried out virtually through a matchmaking app until they both make it to the stage of marriage. In this study, the researcher used a qualitative descriptive study using a phenomenological approach that was initiated by Husserl. The results of this study found that there was social penetration or the process of exchanging information carried out by Tinder users with their partners around the layers of their respective personalities in-depth such as peeling the skins of onions (layers of an onion) during the relationship development process and the process of self-disclosure between users and their partners on Tinder. This study was written using the Van Kaam analysis technique. The results of this study found that there was a relationship development process in which there was a process of social penetration and self-disclosure between key informants and informants in this study during an online relationship on Tinder until they decided to get married.